Genetic inviability is a major driver of type III survivorship in experimental families of a highly fecund marine bivalve. Issue 4 (11th February 2016) - Plough, L. V.; Shin, G.; Hedgecock, D.
Abstract: The offspring of most highly fecund marine fish and shellfish suffer substantial mortality early in the life cycle, complicating prediction of recruitment and fisheries management. Early mortality has long been attributed to environmental factors and almost never to genetic sources. Previous work on a variety of marine bivalve species uncovered substantial genetic inviability among the offspring of inbred crosses, suggesting a large load of early‐acting deleterious recessive mutations. However, genetic inviability of randomly bred offspring has not been addressed. Here, genome‐wide surveys reveal widespread, genotype‐dependent mortality in randomly bred, full‐sib progenies of wild‐caught Pacific oysters ( Crassostrea gigas ). Using gene‐mapping methods, we infer that 11–19 detrimental alleles per family render 97.9–99.8% of progeny inviable. The variable genomic positions of viability loci among families imply a surprisingly large load of partially dominant or additive detrimental mutations in wild adult oysters. Although caution is required in interpreting the relevance of experimental results for natural field environments, we argue that the observed genetic inviability corresponds with type III survivorship, which is characteristic of both hatchery and field environments and that our results, therefore, suggest the need for additional experiments under the near‐natural conditions of mesocosms. We explore the population genetic implications of our results, calculating a detrimental mutation rate that is comparable to that estimated for conifers and other highly fecund perennial plants. Genetic inviability ought to be considered as a potential major source of low and variable recruitment in highly fecund marine animals.